Implementation of IoT-Based Monitoring System at Bottle Capping Assembly Stations Using Haiwell Cloud Box - Ernadi, Yuliadi; Ramdani, Cepi; Quolan Khoerul Auni (LPPM Institut Pendidikan Nusantara Global, 2025)
The transformation of Industry 4.0 has driven the integration of automation and the Internet of Things (IoT) in the manufacturing sector. IoT integration in production systems enables direct manipulation of processes and deeper monitoring of operational conditions, thereby reducing errors and increasing productivity. This study designs and implements an IoT-based monitoring system on a bottle cap assembly station by integrating the Mitsubishi FX5U-32MR/ES PLC and the Haiwell Cloud Box (eBOX-E). The system combines sensors for real-time monitoring, cloud-based remote control, and a SCADA Cloud interface accessible via both desktop web and Android devices. Functional testing of the six-page SCADA Cloud system demonstrated that all system components operated optimally (100% success rate) and were compatible across both desktop web and Android platforms without performance differences. The quality of data transmission using the tested 4G network was rated excellent based on QoS parameter evaluations. These findings indicate that the system enhances monitoring accuracy, reduces human error, and strengthens the role of IoT in boosting industrial productivity through more flexible real-time data access and control.